Manganese-catalyzed direct C-C coupling of -C-H bonds of amides and esters with alcohols via hydrogen autotransfer - Rana, Jagannath; Gupta, Virendrakumar; Balaraman, Ekambaram (Dalton Transactions, 2019)
Herein we report an efficient manganese-catalyzed C-alkylation of unactivated amides and tert-butyl acetate using alcohols as alkylating agents. This elegant approach exhibits a broad substrate scope providing the C-C coupled products of amides via a hydrogen auto-transfer strategy using aryl, heteroaryl, and aliphatic alcohols.